2019
DOI: 10.1016/j.cct.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Testing a behavioral intervention to improve adherence to adjuvant endocrine therapy (AET)

Abstract: Adjuvant endocrine therapy (AET) is used to prevent recurrence and reduce mortality for women with hormone receptor positive breast cancer. Poor adherence to AET is a significant problem and contributes to increased medical costs and mortality. A variety of problematic symptoms associated with AET are related to non-adherence and early discontinuation of treatment. The goal of this study is to test a novel, telephone-based coping skills training that teaches patients adherence skills and techniques for coping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 110 publications
0
14
0
Order By: Relevance
“… 11 Research on technologies that support medication adherence, including adherence among those with cardiovascular conditions, has flourished in recent years. 12–19 These technologies track and/or support adherence through a variety of mechanisms. One such technology is electronic pill bottles, the newest versions of which can not only track pill bottle openings, but also alert patients to missed doses and remotely transmit signals so that clinicians can be alerted of such misses.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Research on technologies that support medication adherence, including adherence among those with cardiovascular conditions, has flourished in recent years. 12–19 These technologies track and/or support adherence through a variety of mechanisms. One such technology is electronic pill bottles, the newest versions of which can not only track pill bottle openings, but also alert patients to missed doses and remotely transmit signals so that clinicians can be alerted of such misses.…”
Section: Introductionmentioning
confidence: 99%
“…44 In a study of 22 breast cancer survivors, semi-structured in-depth interviews identified that social support provides some women with educational, physical, and emotional benefits that may influence their continuation of AET. 45 On-going clinical trials are investigating alternative interventions using telephone-based coping skills training 46 and web-based applications that collects patient-reported symptoms to their healthcare teams 47 . Thus, drawing parallels to endocrine therapy adherence for carcinoma, our study reiterates the currently unmet clinical need for interventions geared specifically towards minimizing racial and ethnic gaps in the use of chemoprevention among high-risk populations of different backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Although the median age at diagnosis was comparable between non-Hispanic white and non-Hispanic black women, Hispanic women tended to be younger at the time of an atypia diagnosis (median age in years [IQR]; Hispanic: 46 [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]; non-Hispanic black: 57 [49-65]; non-Hispanic white: 54 [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]; p=0.05; Table 1). Accordingly, pre-menopausal status was over-represented among Hispanic women (Hispanic: 40%; non-Hispanic black: 15%; non-Hispanic white: 16.9%; p=0.02).…”
Section: Breast Cancer Risk Factors By Remmentioning
confidence: 99%
“…Given past research demonstrating that negative side effects are the leading cause of AET nonadherence [11], leveraging technologies such as the THRIVE app that connect patients with their care teams to facilitate timely changes to clinical management may reduce symptom burden and promote adherence. Other ongoing trials are similarly testing behavioral interventions to increase AET adherence [69, 70], using interactive messaging and nurse-delivered self-management training telephone call to improve symptom coping and side-effect management. An examination of the relative differences between results will be of great interest.…”
Section: Discussionmentioning
confidence: 99%